Turbine wheel study for turbojet engine - Yune, Sebastian Wei Kiat. (2011)
Nanyang Technological University (NTU) has grown her interest in developing, designing and manufacturing a turbojet engine at the institute level due to its high level of involvement in international UAV competitions. There are several Final Year Projects aim to explore the means to design and improve the turbojet engine at component level, such as the compressor, combustor and turbine.